G318(P) The epidemiological basis of acute rheumatic fever: a translatable retrospective study in new zealand. (24th May 2017) - Humby, J; Walsh, L; Malcolm, J
Abstract : Aims: To describe the distribution of Acute Rheumatic Fever (ARF) using deprivation and ethnicity, utilising cases in the Bay of Plenty District Health Board, New Zealand. Background: ARF has a significant associated morbidity and mortality. Thorough understanding of epidemiological associations is important for risk assessment and intervention targeting. The Bay of Plenty (BOP) region in New Zealand (NZ) has a high rate of ARF (34/100, 000) and is therefore a useful population to study this disease. Method: We undertook a retrospective cohort study of those with a principle diagnosis of ARF from 2000–2015 using the NZNHF and Cardiac Society of ANZ criteria 2006–2014. Comparison was made between incidence, ethnicity (Maori, Pacific, European) and deprivation based on residential location (scored using the NZ Deprivation Index 2006 (NZ DEP); 1=least deprived, 10=most deprived). The eastern region (EBOP) was also compared with the western region (WBOP). Data was sourced from medical and 2013 census records. Results: 156 cases were identified, average age 12.6 (2–43), 72% were male (n=113). Increased deprivation was associated with increased incidence of ARF; 49% (n=76) of all cases were found in decile 10 (most deprived), and 12.2% (n=19), were in deciles 1–5. Maori ethnicity represented 90% of cases (35x increased risk compared with non-Maori). The WBOP had a lower general deprivation compared with the EBOP (WBOP=5.9, EBOP=7.3) and average ARF case deprivation reflected this (WBOP 7.0, EBOP=9.4). Further, WBOP ARF cases (n=55) showed a more spread distribution (NZ DEP 1–5; WBOP=25%, EBOP=6%). Maori ethnicity maintained a strong association with ARF cases in the WBOP despite lower deprivation (r=0.98). Discussion: ARF risk was associated with increased deprivation and Maori ethnicity conferred a high risk independently to deprivation. Our results highlight to professionals working with children, including those in the UK, that although ARF is a disease strongly associated with deprivation, social risk factors may be operating irrespectively and should be considered when determining risk.